La carta 67 de S. Cipriano a las comunidades cristianas de León-Astorga y Mérida: Algunos problemas y soluciones - Teja, Ramón (Antigüedad y Cristianismo, 1990)
The author attempts to answer some of the problems of a historical nature raised by the well-known Epistle 67 of Ciprianus of Carthage. He presents historical and gramatical arguments, some of which are proposed for the first time while others are now old but are reworked within the context of the history of the Roman Empire and of the Church in the 3rd century. The aim is to show that Marcial was bishop of Leon-Astorga and was replaced by Felix and that Basilides was bishop of Merida and his successor was Sabino. The author also attempts to explain the existence of a double episcopal see, Leon-Astorga, based on the peculiarities of Leon as cannabae legionis and the rapid spread of Christianity in this legionary sttlement.